Financial risk assessment: case of "Lietuvos Geležinkeliai", AB - Viktorija Skvarciany; Laura Germanaitė (Open Economics, 2019)
This research paper focuses on the analysis of the financial risk of Lietuvos geleézinkeliai, AB (eng. Lithuanian Railways), which activities are passenger and freight transportation by rail. In order to assess the financial risk of the leading company areas of financial risk were identified and are as follows: liquidity risk, credit risk and market risk. However, due to limited access to statistics only financial report of the organisation were analysed and, hence, just liquidity and credit risk were investigated. Consequently, the limitation of the current research is that only two categories of financial risk were analysed. For the purpose of financial risk analysis, the key indicators of liquidity and credit risk were distinguished from the literature. The results showed that the biggest problem of the company is too small short-term assets and the profitability indicators, which were strongly influenced by net profit (loss).
Keywords: G32; 330; financial risk; liquidity risk; credit risk; Lithuanian Railways; case study